Modified Medial Capsulorrhaphy Using Figure-of-Eight Suture in Hallux Valgus Correction Surgery - Raden Andri Primadhi; Ghuna Arioharjo Utoyo; Muhammad Naseh Sajadi Budi; Renaldi Prasetia (Advances in Orthopedics)
Conclusion: While both techniques were efficacious in decreasing HVA, modified capsulorrhaphy using the figure-of-eight technique was better at maintaining corrected HVA until 6-month postoperative period. This technique is recommended because of its efficacy and simplicity.